Analisis Peranan Audit Internal Dan Audit Internal Digital Dalam Upaya Pencegahan Kecurangan Akuntansi (Fraud) - Dwi Wulandari; Ersi Sisdianto (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
Examination of the internal audit function in an effort to identify and stop accounting irregularities (fraud). The purpose of this research is to evaluate the internal audit function in the company's efforts to stop and identify trends in accounting fraud. This research is qualitative in nature and uses a literature review methodology. Secondary data that has been processed to create a picture of research difficulties is used in this research. Internal auditors can conduct assessments and examinations pertaining to the internal control system that a company has installed, based on the findings of research study. Internal auditors, by gaining an awareness of the extent of the organization's overall internal control, can help to ensure that all plans and agendas are carried out in compliance with the company's stated objectives.